COVID‐19 in Spain: Transplantation in the midst of the pandemic. Issue 9 (27th May 2020) - Domínguez‐Gil, Beatriz; Coll, Elisabeth; Fernández‐Ruiz, Mario; Corral, Esther; del Río, Francisco; Zaragoza, Rafael; Rubio, Juan J.; Hernández, Domingo
Abstract : Spain has been one of the most affected countries by the COVID‐19 outbreak. As of April 28, 2020, the number of confirmed cases is 210 773, including 102 548 patients recovered, more than 10 300 admitted to the ICU, and 23 822 deaths, with a global case fatality rate of 11.3%. From the perspective of donation and transplantation, the Spanish system first focused on safety issues, providing recommendations for donor evaluation and testing, and to rule out SARS‐CoV‐2 infection in potential recipients prior to transplantation. Since the country entered into an epidemiological scenario of sustained community transmission and saturation of intensive care, developing donation and transplantation procedures has become highly complex. Since the national state of alarm was declared in Spain on March 13, 2020, the mean number of donors has declined from 7.2 to 1.2 per day, and the mean number of transplants from 16.1 to 2.1 per day. Increased mortality on the waiting list may become a collateral damage of this terrible pandemic. Abstract : The authors present the impact of the COVID‐19 pandemic upon organ donation and transplantation in Spain and provide guidance on donor and recipient evaluation and testing for SARS‐CoV‐2.